Mental health and health behaviors following an economic collapse: The case of Iceland - McClure, Christopher B., 1988- (2014)
Background and aims: Few comprehensive epidemiologic studies exist on the effects of the 2008 economic recession on health outcomes. With Iceland as a prime candidate for examination, the aims of the studies were to explore the effects of the 2008 economic collapse on the mental and behavioral health of an entire population. Design: All aims were ascertained using a cohort (n=4100) of respondents to a mail health survey conducted by the Public Health Institute of Iceland, titled Health and Wellbeing in Iceland. This survey was conducted in two-assessments: (1) between October and December of 2007, (2) between November and December of 2009. The initial study population was based upon a stratified random sample of the Icelandic population. Results: Compared to before the economic collapse, women (odds ratio 1.22; 95% confidence interval 1.04-1.44) – not men – experienced an increased risk of depressive symptoms during recession years. Regardless of sex, a significant increased likelihood of depressive symptoms was observed in the unemployed (1.87; 1.06-3.31) during the recession compared to before. From 2007 to 2009, a significant reduction in the prevalence of smoking was observed in both men and women. At the individual level, male former smokers who experienced an income reduction (0.37; 0.16, 0.85) during the same period were less likely to relapse compared to those with a stable income. There was no evidence for a reduction in or decreased likelihood of visiting a dental health practitioner. Males were more likely to brush (1.42; 1.05–1.93) and floss (1.20; 1.03–1.42) daily during recession years compared to before. Conclusion: The results indicate that the economic collapse and recession in 2008 negatively affected the mental health of the adult population in Iceland, specifically women. However, while mental health was impaired, the economic downturn was related to an increase in the adoption of healthier behaviors.